MINAT INVESTASI MAHASISWA DI PASAR MODAL DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Komang Krishna Yogantara (Journal of Applied Management and Accounting Science, 2021)
The purpose of this study is to determine the effect of investment motivation on student investment interest, to determine the effect of investment knowledge on student investment interest, to determine the effect of minimum investment capital on student interest. The population in this study were 192 students of the Accounting Study Program, Faculty of Business & Social Humanities, Triatma Mulya University in the 2019/2020 academic year. The sampling method was purposive sampling. The number of samples obtained was 156 samples. The test instruments were analyzed using validity and reliability tests. The data analysis technique used is the classical assumption test, multiple linear regression test, t test and F test. The results of this study are that investment motivation (X1) has a positive effect on student investment interest, investment knowledge (X2) has a positive effect on student investment interest. , the minimum investment capital (X3) has a negative effect on student investment interest.